THE IMPACT OF CLIMATE CHANGE ON ASEAN RICE PRODUCTION IN SHORT AND LONG-RUN - Jarita Duasa; Nurhasya Adibah Mohd-Radzman (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
There has been a growing concern over the escalating signs of climate change that could adversely affect the production of rice in ASEAN region. This study attempts to assess the impact of climate change on food security measured in terms of rice yield, with the focus being on ASEAN member countries. Panel data are collected on nine ASEAN countries and static panel data equations are estimated. In addition, the dynamic panel ARDL technique is also adopted to investigate the long-term and short-term cointegration between the variables. The findings show mixed results of impact of CO2 on rice yield among majority of ASEAN member countries in short-run which signify the positive CO2 fertilization effect in the region over the adverse impact of temperature increase on rice yield. In long-run, however, the negative effects are projected which might reduce rice yield in this tropical area. Thus, serious collaboration between developing and least-developed countries in the region to address the issues in agriculture and rice production is very crucial to solve food insecurity within the region in the long-term.